Test-driven iOS development with Swift : create fully-featured and highly functional iOS apps by writing tests first - Hauser, Dominik (Community experience distilled., 2016)
Create fully-featured and highly functional iOS apps by writing tests first About This Book Learn test-driven principles to help you build apps with fewer bugs and better designs Become more efficient while working with Swift to move on to your next project faster! Learn how to incorporate all of the principles of test-driven development (TDD) in to your daily programming workflow Who This Book Is For If debugging iOS apps is a nerve-racking task for you and you are looking for a fix, this book is for you. What You Will Learn Implement TDD in swift application development Get to know the fundamentals, life cycle, and benefits of TDD Explore the tools and frameworks to effectively use TDD Develop models and controllers driven by tests Construct the network layer using stubs Use functional tests to ensure the app works as planned Automate and streamline the building, analysing, testing, and archiving of your iOS apps In Detail Test-driven development (TDD) is a proven way to find software bugs early. Writing tests before your code improves the structure and maintainability of your app. Test-driven iOS Development with Swift will help you understand the process of TDD and how it impacts your applications written in Swift. Through practical, real-world examples, you'll start seeing how to implement TDD in context. We will begin with an overview of your TDD workflow and then deep-dive into unit testing concepts and code cycles. We will showcase the workings of functional tests, which will help you improve the user interface. Finally, you will learn about automating deployments and continuous integration to run an environment. Style and approach This is an easy-to-follow example-driven tutorial, packed with lots of tips and tricks that explore TDD bit-by-bit in the process of making an iOS application.